Kinetic modeling of gas-phase phenol hydrodeoxygenation over Ag/TiO2 catalyst via TGA-FTIR based microreactor / Andrew Ng Kay Lup - Andrew Ng , Kay Lup (2019)
Bio-oil produced from biomass pyrolysis is a potential source for liquid fuel. However, bio-oil has high oxygen content due to its complex mixture of oxygen-containing compounds which results in deleterious properties such as lower heating value, corrosion and chemical instability of liquid fuel. Phenolics are some of the major O-containing constituents commonly found in lignocellulosic biomass derived bio-oil. Thus, phenolic hydrodeoxygenation (HDO) is a process required for bio-oil upgrading into high quality liquid fuel. In this study, gas-phase hydrodeoxygenation of phenol over Ag/TiO2 catalyst at atmospheric pressure was conducted as a model compound approach in investigating the reaction mechanism and kinetics of oxygen removal from phenolics. Physicochemical properties of Ag/TiO2 catalyst were investigated to explore its potential as hydrodeoxygenation catalyst. The results showed that the metal-support interaction of Ag/TiO2 enabled hydrogen spillover phenomenon and synergistic interaction of acid and metal sites which are fundamental in catalyzing adsorption and activation of phenolics and hydrogen during hydrodeoxygenation. Reduction study of Ag/TiO2 by hydrogen also showed that Ag2O undergoes single-step reduction to form Ag which can be described using unimolecular decay model. Sample encapsulation technique was also proposed in this study to lengthen the release of vaporized phenol sample in microreactor. The delayed volatiles release phenomenon was enhanced by using metal capsule with higher material hardness and smaller surface area for sample evaporation. By using cylindrical tin capsule, significant release of vaporized phenol was extended up to 454—554 K which is above its boiling point. This finding is useful in enabling better catalyst activation and kinetic study of catalytic solid-gas reaction over a larger temperature range but at a fixed reactant amount. FTIR and GC-MS analyses showed the conversion of phenol into benzene as major product over Ag/TiO2 catalyst at atmospheric pressure condition. The proposed kinetic model for the phenol HDO network over Ag/TiO2 confirmed the occurrence of phenol hydrogenolysis and hydrogenation; cyclohexanol dehydration and hydrogenation of benzene and cyclohexene. The reaction rates increase with the following order: r1 (phenol hydrogenolysis) < r2 (phenol hydrogenation) < r5 (benzene hydrogenation) < r3 (cyclohexanol dehydration) < r4 (cyclohexene hydrogenation). Both phenol hydrogenolysis and hydrogenation steps are the respective rate-limiting steps for DDO (direct deoxygenation) and HYD (hydrogenation-dehydration) pathways of phenol hydrodeoxygenation over Ag/TiO2. Application of transition state theory has also indicated formation of more orderly activated complexes in the elementary reaction steps as indicated by the negative entropy change of activation. The proposed kinetic model was able to describe quantitative and qualitative observations in this work with a reasonable agreement and would be a useful tool for kinetic and mechanistic understanding of surface reactions of phenol HDO over supported transition metal catalysts. Successive hydrodeoxygenation runs (4 h) showed no significant degradation in catalytic and physicochemical properties of Ag/TiO2 catalyst. The accumulation of oxidized Ag metal species and coke deposits on Ag/TiO2 catalyst after each HDO run can be removed via H2-activation and calcination in air at 553 K with at least 98.9% removal efficiency.